UPAYA MENINGKATKAN PARTISIPASI DAN HASIL BELAJAR SISWA KELAS V SD DALAM MATERI BANGUN DATAR MELALUI MODEL PROBLEM BASED LEARNING (PBL) DENGAN MEDIA VISUAL DI SD NEGERI 108/IV KOTA JAMBI - Salsabila, Talitha; Sastrawati, Eka; Noviyanti, Silvina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ participation and learning outcomes in mathematics, particularly on plane geometry material, through the implementation of the Problem Based Learning (PBL) model supported by visual media. The research was conducted at SD Negeri 108/IV Kota Jambi involving 24 fifth-grade students using Classroom Action Research (CAR) consisting of two cycles, each including planning, action, observation, and reflection stages. The initial condition showed low student participation (51.3%) and low learning mastery (47.4%), indicating the need for instructional improvement. In Cycle I, the application of PBL with visual media began to show positive results, with student participation increasing to 68.4% and learning mastery reaching 63.2%, although it had not yet met the success criteria. Improvements were then made in Cycle II by optimizing group work, instructions, and the use of visual media. The results showed a significant increase in student participation to 86.8% (very good category), followed by improved learning outcomes that met the expected mastery criteria. These findings indicate that the implementation of the PBL model combined with visual media effectively enhances both student participation and learning outcomes in learning plane geometry. Therefore, this approach can be used as an alternative strategy to create more active, meaningful, and effective learning in elementary mathematics.